Non-destructive Characteristics of Ultrasonic Waves in 1018 Low Carbon Steel - Kien, Do Trung; Nhung, Pham Thi Tuyet; Thanh, Pham Van (Communications in Physics, 2014)
In this paper, the dependences of the velocities and the absorption coefficients of ultrasonic waves transmitted in 1018 low carbon steel on temperature ranging from 0\(^{°}\)C to 50\(^{°}\)C were investigated. It was shown that the velocities of the ultrasonic longitudinal wave and ultrasonic shear wave were decreased when the temperature increased. The transportation of the ultrasonic longitudinal wave and ultrasonic shear wave depends on temperature and its coefficient in a temperature range of (0 - 50 \(^{°}\)C) was estimated about 0.8 m/s.\(^{°}\)C and 0.44~m/s.\(^{°}\)C, respectively. These obtained results are in good agreement with the theoretical prediction. Furthermore, the absorption coefficients of the ultrasonic longitudinal wave were also studied.